"To think so as to speak" The developmental consequences of languages use in teaching and learning in a primary school in Zimbabwe - SIBONOKUHLE NIL NDLOVU (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2012)
This article is based upon research that was carried in a rural school in Zimbabwe during the period 2010. The research problem in this study was the relationship in teaching, learning and cognitive development as elaborated by Vygotsky's socio-cultural framework. Vygotsky argues that the socio-cultural context impacts significantly on the learner's cognitive development. This study investigated specifically the aspect of the use of the Language of Teaching and Learning (LOTL) as an aspect that significantly influences teaching, learning and consequently cognitive development. This study was a response to Vygotsky's (1978) cautioning against neglecting to consider the underlying causes that can be influential factors in the socio-cultural context and considering only surface and obvious ones.   Thus, the study particularly examined the impact of the use of language in teaching and learning on learners' cognitive development, using the Vygotskian theoretical conception of language and thought, in a cultural context of rural Zimbabwe schooling.  A case study of one rural primary school has been used and data collection involved observation of classroom teaching and learning to find out how language is used and how learners respond during the learning process.  The findings of the study were that teachers simultaneously use two language codes of English and native language of Ndebele as the mixed language code. Use of language this way is so as to help learners who are not the first speakers of English to understand concepts being taught in different subjects. However this has been found to have limitations in the development of both languages consequently impacting negatively on concept development and failure by learners to participate fully in learning activities. The article contributes to an understanding of the effects of the use of language on learners learning and cognitive development specifically and suggests ways in which teachers could effectively use language to assist their learners' learning, cognitive development and understanding of concepts during learning.